THE EFFECT OF PRODUCT QUALITY, PERCEIVED PRICE AND ACCESSIBILITY ON CUSTOMER SATISFACTION: AN EMPIRICAL STUDY IN INDONESIAN RESTAURANTS - Ridwan Ari Saputra; Jamaludin Khalid (Strategic Management Business Journal, 2023)
This study examines the effect of product quality, price perception, and accessibility on customer satisfaction at STEAK 21. X1 is product quality, X2 is price perception, X3 is accessibility, and Y is customer satisfaction. This study used a survey-based quantitative research design using a purposive sampling sample with 30 respondents. This study uses primary data or data collected directly from respondents who came to steak restaurant 21, including their perceptions of aspects of product quality, price perception, and accessibility with the number of respondents as many as 100 respondents. Thus the data collected in this study was 130 data or respondents. Based on the results of the analysis in this study using validity tests, reliability tests, descriptive analysis, data normality tests, heterochedasity tests, multicollinearity tests, linearity tests, multiple linear regression tests, t-tests, f tests, correlations and coefficients of determination that produce a description, namely, There is a significant influence between product quality (X1) on customer satisfaction (Y) with a significant value of 0.002 < 0.05, there is a positive influence and significant in the price perception variable (X2) to customer satisfaction (Y) with a significant value of 0.000 < 0.05 and accessibility (X3) on STEAK 21 also had a significant influence on customer satisfaction on STEAK 21 (Y) with a significant value of 0.002 < 0.05. Finally, the combined findings suggest that product quality, price perception, and accessibility significantly influenced consumer satisfaction at STEAK 21. JEL Classification: M31, O14